1990
DOI: 10.1002/em.2850160308
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Salmonella (Ames) test, Umu tests, and the sos chromotests for detecting genotoxins

Abstract: The limits of detection of 10 genotoxins representing 7 chemical classes with varying structures and modes of action were compared using the Ames test (Salmonella plate-incorporation test) with 2 tester strains, 2 standard colorimetric methods (the umu test and SOS Chromotest), and modifications of the umu and SOS Chromotests developed during the course of this study. The purpose of the study was to determine the sensitivity and reproducibility of each of the six methods. The sensitivities of the methods were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 14 publications
1
21
0
3
Order By: Relevance
“…For example, 32 PAHs tested by Mersch-Sunderman et al (1992) using the SOS Chromotest were shown to be more potent with S9 mix. Sensitivity of the SOS Chromotest with cyclohexane and methylene chloride extracts of soils from hazardous waste sites was greater with S9 mix than without (McDaniels et al, 1990). Again, the genotoxicity of water and sediment extracts was reported to be generally lower and higher, respectively, in the presence of S9 mix (Langevin et al, 1992).…”
Section: Influence Of S9 MIX On Sample Toxicity and Genotoxic Activitymentioning
confidence: 94%
See 1 more Smart Citation
“…For example, 32 PAHs tested by Mersch-Sunderman et al (1992) using the SOS Chromotest were shown to be more potent with S9 mix. Sensitivity of the SOS Chromotest with cyclohexane and methylene chloride extracts of soils from hazardous waste sites was greater with S9 mix than without (McDaniels et al, 1990). Again, the genotoxicity of water and sediment extracts was reported to be generally lower and higher, respectively, in the presence of S9 mix (Langevin et al, 1992).…”
Section: Influence Of S9 MIX On Sample Toxicity and Genotoxic Activitymentioning
confidence: 94%
“…In addition to economy, this technique offers several practical advantages (Legault et al, 1994). Over the years, the SOS Chromotest was shown to correlate well with the Ames tests in detecting mutagens (Otha et al, 1984;Von der Hude et al, 1988;McDaniels et al, 1990). More recent articles have confirmed this fact (Quillardet and Hofnung, 1993;Legault et al, 1994, Mersch-Sundermann et al, 1994White and Rasmussen, 1995).…”
Section: Ntro Du Ct 1 0 Nmentioning
confidence: 95%
“…This demonstrates that the compounds causing genotoxic e!ects are transformed by enzymatic activity. The di!erence between the tests results reveals that the response of the di!erent bacteria varies (McDaniels et al, 1990;Oda et al, 1995). For this reason several tests should be performed, if the occurrence of genotoxic e!ects is to be excluded.…”
Section: Methodsmentioning
confidence: 99%
“…SOS-Chromotest, a simple bacterial colorimetric assay, was used in this study for testing genotoxicity. Scientific literature has reported the sensitivity of this test for AFB1 [11][12][13] and high correlation (60-100%) with the widely used Ames test [12,[14][15][16][17][18][19]. Our aim was to develop bacterial biotests for monitoring mycotoxins and screening mycotoxin degrading microbes.…”
Section: Introductionmentioning
confidence: 99%